INTERCULTURAL ENCOUNTER AND CHRISTIANITY TODAY - Sugiharto, Bambang (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2009)
Intercultural encounter is something inevitable and crucial today. Its significance for religions depends on how religions conceive of intercultural translatability and the meaning of ‘the other’. Concerning the former, there are three possibilities : different cultures can be seen as radically untranslatable, mutually translatable in terms of universal economic medium, or mutually translatable in terms of universal doctrinal message. Each brings its own consequences. Concerning the latter, the other may be viewed as the outer-other or the inner-other of which both require some kind of self-relativization on the part of religion. If Christianity is consistent with its ‘logic of love’, it would be governed by heteronomous reason in which the self lives from out of itself , whereas its dwelling place is not the privileged centre.